Effect of ethanol as gasoline additive on vehicle fuel delivery system corrosion - Jafari, Hassan (John Wiley and Sons Ltd, 2010)
In this research, the effect of ethanol as gasoline additive has been investigated into metal corrosion of a fuel delivery system. Corrosion tests have been performed in gasoline with different percentages of ethanol, using weight loss (immersion test) and electrochemical impedance stereoscopy (EIS) procedures. Surface of test specimens were checked by scanning electron microscopy (SEM) after 144 days of immersion in test solution. Also corroded components were analyzed using energy-dispersive X-ray analysis (EDAX) method. Test results, investigations, and analyses, altogether show more corrosion with the increase in ethanol percentage and water content in gasoline. Test results show that among different materials in fuel delivery system, aluminum alloys and hard soldering alloys have less corrosion than the others. Also chloride and sulfide were recognized as the main compound of corrosion products; therefore, the control of these two elements in fuel delivery system is a must in case of using ethanol as fuel additive in near future.